Analisis dan Model Standard Angkutan Laut: Studi Kasus Muatan Petikemas - Achmadi, Tri; Abdan Hanif, Mohammad; Sina Khaqiqi, Alwi (Universitas Trunojoyo Madura, 2021)
The increase in container rates, which tends to be unstable, has an impact on the price of cargo per unit to increase. The uncertainty of the amount of cargo carried makes the tariffs imposed also unstable. The purpose of this research is to make a standard model of the cost of each unit and the size of the capacity of container transport services based on changes in cargo and distance of shipping routes. In addition, it analyzes the relationship between load factor and frequency on the gross income of a shipping company. The optimization method is used to get the size and cost per unit under certain conditions. The results of the analysis explain that the current tariff is not yet optimal, proven by the current cost equation y=2E+06x(-0,342) (R2= 0,238). Then to create a standard model of transportation, the equation for the cost line per container ship freight unit y=1E+09x(-0,759) (R2= 0,8634) while SPCB y=6E+07x(-0,59) (R2 = 0,8234). This study also produces an equation model for the size of the container ship transport capacity y=3E-05x+57,662 (R2=0,943) while SPCB y=2E-05x+94,446 (R2=0,997). The conclusion is using a sensitivity analysis of the carrying capacity with the current condition of ship operation patterns for the minimum load factor for the Surabaya-Ambon route 76% and Surabaya-Serui 48%. For a 100% load factor condition, it can reduce the cost per unit for the Surabaya-Ambon route by 50% and for the Surabaya-Serui route by 63%.